Is the Equity Market Really Developed in the People's Republic of China? - Sayuri Shirai (Asian Development Bank Institute (ADBI), 2002)
Since two domestic stock exchanges were established in the Peoples Republic of China (PRC) in the early 1990s, equity market growth has been remarkable. Nevertheless, the closer scrutiny reveals that the market is highly segmented and distorted. This paper assesses the state of the PRCs equity market development by focusing on its following three main functions(1) a source of stable financing for firms investment, (2) improving firms corporate governance and performance, and (3) signaling information on issuers to public investors. It concludes that the equity market has so far failed either to provide stable sources of finance for firms investment or improve their performance (indeed, firms performance has even deteriorated following initial public offerings). Moreover, while firms fundamentals have been reflected to a large extent in stock prices, suggesting that there is at least some signaling role, their co-movement has declined in recent years despite clampdowns against accounting malpractices. Indeed, it is likely that co-movement between stock prices and earnings per share has encouraged accounting manipulations to bump up stock prices. These findings suggest that PRCs equity market remains underdeveloped. If the Government is to privatize listed SOEs, the governance needs to introduce measures to prevent asset striping undertaken by managers of SOEs. Moreover, if the Government needs to develop a sound equity market, it must urgently improve the informational, legal, and judicial infrastructure, and educate public investors.
hdl:11540/4147
Keywords: 330